Dr. Igor Lishchynskyy celebrate 50 anniversary - PCSS, Editorial Board (Physics and Chemistry of Solid State, 2021)
Ph.D., Assoc. Prof. Lishchynskyy Igor Myroslavovych, Head of the Department of Physics and Teaching Methods of Vasyl Stefanyk Precarpathian National University, Candidate of Physical and Mathematical Sciences, member of the organizing committee of the International Conferences on Physics and Technology of Thin Films and Nanosystems and editor of the journal 'Physics and Chemistry of Solid State'.